El Tercer Bronce de Botorrita, veinte años después (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Reviewing the text of the Third Botorrita Bronze, found in 1992, the article shows that: 1) the foreign PNN indicate the inscription to be comparatively modern; 2) several of the Celtic names are theophoric, among them Ebursunos ‘Son of the god EBUROS’, which preserves an important relic of the inherited IE lexicon; 3) some of the alleged idionyms are not names; 4) several of the denominations of social groups refer to occupation or provenance. It also (5) improves the translation of some parts of the inscription’s heading and list and (6) adds evidence in favour of the interpretation of the Third Bronce as a concession of water rights (cf. PalHisp 7/2007).
Keywords: Celtiberian Epigraphy; Celtiberian Society; Celtic Lexicon; Personal Names; Water